Advances and Challenges in Using Ammonia as a Hydrogen Carrier for a Sustainable Energy Future - Zhou Yuanhao (MATEC Web of Conferences)
Ammonia is rapidly emerging as a critical player in the global shift toward hydrogen-based energy, which offers a practical answer to one of the clean energy transition’s toughest challenges: How to store and move hydrogen efficiently. With a hydrogen content of 17.6 wt% and a volumetric density of 121 kg H₂/m³, which is nearly double then that of liquid hydrogen, ammonia provides efficient, large-scale storage and transport capabilities. Its ability to liquefy under mild conditions allows it to tap into a vast existing infrastructure built for agricultural use, making it a cost-effective alternative to traditional methods. Recent breakthroughs in catalytic decomposition have boosted its potential, with non-precious metal catalysts like hierarchical Ni/Al₂O₃ and Fe–N–C single-atom catalysts showing improved activity and stability, while noble metal catalysts, such as ruthenium on lanthanum nitride supports, achieve high performance at lower temperatures. Innovations like plasma-assisted and photocatalytic decomposition are also emerging, which offers energy-efficient and sustainable ways to release hydrogen. While on the production side, green ammonia synthesis, which means people use renewable energy through electrocatalytic, photocatalytic, and biological methods—is advancing, though high costs remain a hurdle. Ammonia’s role as a carbon-free carrier is key for decarbonizing tough sectors like shipping, aviation, and steelmaking, which contribute 15–20% of global CO₂ emissions. Still, challenges like catalyst durability, integration with spasmodic renewables, and energy-intensive decomposition persist. Overcoming these through ongoing innovation is critical to let ammonia be totally widely accessible and affordable.